Superconducting properties of bulk Bi1.6Pb0.4Sr2Ca2− xCdxCu3O10 system prepared via conventional solid state and coprecipitation methods - Hamadneh, Imad; Agil, A.; Yahya, Ahmad Kamal; Shari, Abdul Halim (Elsevier, 2007)

(untitled)
The effect of Cd doping on the superconducting properties of BSCCO system with nominal starting compositions of Bi1.6Pb0.4Sr2Ca2−xCdxCu3O10 (x = 0.00–0.10) was studied. The preparation methods used to prepare the samples are the conventional solid-state oxide powder (SSR) and the coprecipitation (COP) techniques. Resistivity versus temperature measurements (R–T) showed that all doped samples exhibited metallic behaviour. For the SSR samples, existence of a two step feature was observed at x = 0.07 indicating the presence a lower temperature 2212 phase together with the higher temperature 2223 phase. This behaviour resulted in the shifting of the TC(R=0) towards lower temperature. However, the COP samples showed better superconducting properties probably due to higher homogeneity resulted from mixing of sub-micron particles during sintering. The R–T curve did not display any two step features due to the single phase nature of the samples. This is confirmed by the XRD data where Bi-2212 phase was minor. In addition, small amount of doping (x = 0.02 in COP and SSR samples) enhanced the phase formation and TC(R=0).